Ubiservices: A Connectivity Model to Ubiquitous Environments - Brand, Gustavo B.; Garzão, Alex; Barbosa, Jorge L. V.; Ávila, Rafael (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2010)
With the fast evolution of the computing devices, its reduced size and cost, there is an immersion of people in the digital world. With the use of more technology, abundant and cheap, environments that can take advantage of the ubiquitous computing emerge, allowing its users to interact and have access to information easily, quickly and naturally. However, classic ubiquitous environments were defined needing a large installed infrastructure to work properly, something that is not a reality nowadays. This work presents an alternative to the classic ubiquitous environments: a model of services connectivity called Ubiservices, that focuses on providing connectivity to environments made up of unstructured Ad Hoc networks.